2021
DOI: 10.1002/slct.202100511
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Active Phase in Pd‐Based Catalysts Supporting on Octahedral CeO2 for Low‐Temperature Methane Oxidation

Abstract: Pd catalysts supported on CeO 2 (Pd/CeO 2 ) are highly active towards lean methane combustion, and the catalytic behavior is substantially affected by the chemical property of surface palladium species. In this work, various Pd catalysts supported on octahedral-CeO 2 (Pd/O-CeO 2 ) were successfully prepared by redox interation-engaged strategy. The oxidation state of palladium species was controlled by varying the calcination condition. X-ray absorption characterization coupled with lightoff curves confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Regarding previous research, [5] the peak located at 529.3 eV can be identified as the lattice oxygen (O α , e.g, O 2− ), the binding energy situated at 531.1 eV can be attributed to the adsorbed oxygen components (O β , e.g, O 2 2− , O 2 − or O − ), and the binding energy at 533–534 eV can be caused by the weak‐bonded oxygen species (O γ ) [2b] . As compiled in Table 2, the O β /(O α +O β ) ratio is a measurement to appraise the ratio of reactive oxygen components [40] . The proportion of O β /(O α +O β ) for CeO 2 , 5 %Cu@CeO 2 , 0.5 %Ir@CeO 2 , 2Cu0.5Ir@CeO 2 , 5Cu0.5Ir@CeO 2 and 10Cu 0.5Ir@CeO 2 samples were approximately 22.5 %, 24.3 %, 34.8 %, 35.1 %, 45.6 % and 36.6 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding previous research, [5] the peak located at 529.3 eV can be identified as the lattice oxygen (O α , e.g, O 2− ), the binding energy situated at 531.1 eV can be attributed to the adsorbed oxygen components (O β , e.g, O 2 2− , O 2 − or O − ), and the binding energy at 533–534 eV can be caused by the weak‐bonded oxygen species (O γ ) [2b] . As compiled in Table 2, the O β /(O α +O β ) ratio is a measurement to appraise the ratio of reactive oxygen components [40] . The proportion of O β /(O α +O β ) for CeO 2 , 5 %Cu@CeO 2 , 0.5 %Ir@CeO 2 , 2Cu0.5Ir@CeO 2 , 5Cu0.5Ir@CeO 2 and 10Cu 0.5Ir@CeO 2 samples were approximately 22.5 %, 24.3 %, 34.8 %, 35.1 %, 45.6 % and 36.6 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[2b] As compiled in Table 2, the O β /(O α + O β ) ratio is a measurement to appraise the ratio of reactive oxygen components. [40] The proportion of O β /(O α + O β ) for CeO 2 , 5 %Cu@CeO 2 , 0.5 %Ir@CeO 2 , 2Cu0.5Ir@CeO 2 , 5Cu0.5Ir@CeO 2 and 10Cu 0.5Ir@CeO 2 samples were approximately 22.5 %, 24.3 %, 34.8 %, 35.1 %, 45.6 % and 36.6 %, respectively. Therefore, the O 1s and Ce 3d XPS spectra prove that the CuÀ Ir@CeO 2 catalysts can release more adsorbed oxygen and oxygen vacancies, which is responsible for the catalytic performance of methane.…”
Section: Chemical State and Electronic Structurementioning
confidence: 90%
“…The T 90 CH 4 conversion for static air calcinated samples (Pd/CeO 2 S-x, where x stands for calcination time) were 415, 370, 349, 368, and 390 °C for Pd/CeO 2 S-0.5, Pd/CeO 2 S-1, Pd/CeO 2 S-2, Pd/CeO 2 S-3, and Pd/CeO 2 S-5, respectively. [74] Thus, within limits, increasing Pd 0 /PdO ratio can decrease the activation temperature of CH 4 . Jian et al reported similar results, using the reduction-deposition and impregnation method (IMP) to make 3 Pd/CeO 2 catalysts with various chemical and electronic states of Pd species, using hydrazine hydrate (HHA) and formaldehyde (FA) as reductants, respectively.…”
Section: Pd-based Catalystsmentioning
confidence: 98%
“…The T 90 CH 4 conversion for static air calcinated samples (Pd/CeO 2 S‐ x , where x stands for calcination time) were 415, 370, 349, 368, and 390 °C for Pd/CeO 2 S‐0.5, Pd/CeO 2 S‐1, Pd/CeO 2 S‐2, Pd/CeO 2 S‐3, and Pd/CeO 2 S‐5, respectively. [ 74 ] Thus, within limits, increasing Pd 0 /PdO ratio can decrease the activation temperature of CH 4 . Jian et al.…”
Section: Thermocatalytic Activation Of Methanementioning
confidence: 99%
See 1 more Smart Citation